2013
DOI: 10.1007/s40272-013-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacoepidemiology of Selective Serotonin Reuptake Inhibitors for Children and Adolescents in Canada from 2005 to 2009: A Database Analysis

Abstract: The increase in use of SSRIs in Canadian children and adolescents from 2005 to 2009 suggests that the effects of public health warnings concerning suicidal thinking and behavior associated with these drugs are now dissipating. This may be attributable to the FDA's pediatric approvals for fluoxetine and escitalopram, the growing comfort of clinicians with using SSRIs in children, limited availability of psychosocial treatments, and the influence of marketing. The use of paroxetine has continued to decline, like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
2
28
0
1
Order By: Relevance
“…The data have been used previously to evaluate prescribing trends. [10][11][12] We requested further information on data collection; however, IMS Brogan does not release details regarding which pharmacies contribute to their database. Data for the same period were available from both sources and were compared to evaluate consistency of the findings.…”
Section: Data Collectionmentioning
confidence: 99%
“…The data have been used previously to evaluate prescribing trends. [10][11][12] We requested further information on data collection; however, IMS Brogan does not release details regarding which pharmacies contribute to their database. Data for the same period were available from both sources and were compared to evaluate consistency of the findings.…”
Section: Data Collectionmentioning
confidence: 99%
“…Consequently, the sustained high use of antipsychotics observed in this study raises concerns, especially in view of recent recommendations cautioning against the use of these drugs for the treatment of non‐psychotic disorders and the demonstrated effectiveness of behavioural non‐pharmacological treatments, such as behaviour modification . The moderate decrease in use of SSRIs, the most commonly prescribed class of antidepressants, between 1999 and 2008 may be explained by reports of the risk of suicide and suicidal ideation among young users, as well as safety advisories issued during this time by regulators in countries such as Canada, the United States and the United Kingdom …”
Section: Discussionmentioning
confidence: 99%
“…In an aim to advance medication safety for children, an understanding of paediatric prescribing trends is required to identify the type and prevalence of medications prescribed, particularly those that are associated with high‐risk adverse events. To date, most studies on prescribing trends in children have focused on the inpatient setting or on specific drug categories, such as antipsychotics, antidepressants and medications used to treat attention‐deficit/hyperactivity disorder (ADHD) . These studies have revealed important changes in paediatric prescribing over time; however, most reflect a narrow examination of specific drug classes, producing a gap in understanding overall prescribing trends.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of suicidal behavior at the early "activatory" stage of treatment [62] requires close monitoring, though suicidal tendencies are also high at the remission stage because of patients' low stress resistance, especially when they lack psychological support. In connection with these methodological limitations, data on suicidal tendencies require a balanced approach and obligatory modifi cations for subpopulations consisting of children and adolescents [63], particularly as prescription of SSRI (escitalopram) to children and adolescents becomes more frequent [64].…”
mentioning
confidence: 99%